ANALISIS PERTUMBUHAN EKONOMI KOTA DAN KABUPATEN PADA KAWASAN METROPOLITAN BANJARBAKULA - Muhammad Yospi Maurizki Anugrah; Ryan Juminta Anward (PPJP Universitas Lambung Mangkurat, 2020)
This research is a quantitative descriptive study by processing and analyzing economic growth data, location quotient values, shift share and typology klassen in the Banjarbakula Region. The type of data used for analysis is secondary data in the form of time series between 2014-2018 obtained from BPS in each Banjarbakula region.The results showed that the LQ value for each region of the Banjarbakula region was different and had a different leading sector. This makes the Banjarbakula Region have advantages in each sector which is divided in each region. Economic growth in the city and district of Banjarbakula is increasing from 2015-2018. The total GRDP of the Banjarbakula Region as a whole also experienced an increase of Rp 6,369,560,000,000.21. The growth of each sector in Banjarbakula is also in three different quadrants and the most dominant is in the fast-growing sector.Keywords: Economic Growth, Banjarbakula, South Kalimantan, Location Quotient, Shift Share, Typology Klassen.